Development of a drainage and flood control management program for urbanizing communities. Part I - Riordan, Eugene J., author; Grigg, Neil S., author; Hiller, Robert L., author; Environmental Resources Center, publisher (Colorado State University. Libraries, 1978)
Urbanization causes an alteration of the stormwater runoff response of the urbanizing watershed which, in turn, increases stormwater damages downstream. Few communities have successfully implemented programs for managing these development induced drainage impacts due in part to the uncertainties associated with any drainage management program. Which rainfall-runoff model should be used, how sensitive is project analysis to poor discharge prediction, how should project cost be allocated, and so on. The objective of this research is to clarify these uncertainties and develop a readily implementable drainage and flood control management program for the mitigation of development-induced drainage impacts. These objectives are realized through a detailed examination of and recommendation on the three major elements of a drainage management program: the Technical element which establishes the method of flood hydrology calculation, the Financial element which establishes the methods for drainage and flood control cost calculation and cost allocation, and the Regulatory element which establishes the enforcement mechanism of the drainage management program. The recommended Technical element is based on the sensitivity of project analysis to poor runoff prediction, and on the predictive capability of various rainfall-runoff models. This predictive capability was evaluated for some of the more popular rainfall-runoff models through a statistical analysis of published results from those models. The recommended Financial element is based on a thorough review of the legal issues regarding: 1) municipal and developer liability with respect to development-induced drainage impacts, 2) project cost calculation, and 3) project cost apportionment. A new approach for apportioning drainage and flood control facility costs between developers and the municipal government is presented. The approach utilizes existing engineering analysis techniques to divide project costs in proportion to the reduced liability attributable to the developers and to the municipal government. Two Regulatory elements are proposed for the drainage management program. The changes to existing legislation that are necessary to enforce the drainage management program under the proposed regulatory component are discussed and sample legislation is included for each. The report is divided into two parts. Part II is the complete project report with detailed discussions of the methods and data used, and of the research findings. Part I is written as a user publication. It summarizes the research methods and results, and discusses the recommended drainage management program.
Submitted to Office of Water Research and Technology, U.S. Department of Interior.
September 1978.
Keywords: Flood control -- United States; Flood control